Factors that Affect Coping Mechanisms in Chemotherapy Patients with the Approach of Callista Roy Adaptation Theory - Ifa Roifah; Elies Meilinawati; Tri Ratnaningsih; Rina Nur Hidayati (Journal of Ners and Midwifery, 2019)
Chemotherapy could cause pain in the patient, thus causing the condition of the body would gradually weaken. This condition would make the patient delay the therapy due to physical symptoms and emotional pressure (psychological), which affected the seriousness of patients in the treatment and strong coping mechanism required to maintain good conditions One of the empirical evidence of conceptual model theory "Holistic Adaptif System", Callista Roy put it, this model was used in chronic illnesses undergoing treatment, because theoretically successful handling by conducting adaptive coping mechanism behavior was an important variable in the physiological and psychological adaptation process to the stimulus that occurs. This study aimed to identify the behavior of patients using Callista Roy adaptology. This study aimed to analyze factors that influenced coping mechanisms in chemotherapy patients with the Callista Roy adaptation theory approach. This research design is analytical with a cross sectional approach. The population in this study were 95 patients. This research sampling technique was Consecutive Sampling. The sample size in this study was 78 respondents who met the criteria of the researcher. The research instrument used CAPS with an adaptation theory approach. The results showed that educational factors (p = 0.031) and job (p = 0.023) influenced the coping mechanism with the theory approach of Callista Roy adaptation to chemotherapy patients. The higher the level of education, the tolerance and control of stressors is better so that coping mechanisms become adaptive. Those who worked were more stress because they had to combine their work with scheduled care.